Antioxidant trace elements serum levels in long-term parenteral nutrition (PN): Prevalence and infectious risk associated with deficiencies, a retrospective study from a tertiary home-PN center. Issue 3 (June 2017) - Uzzan, Mathieu; Kirchgesner, Julien; Poupon, Joël; Corcos, Olivier; Pingenot, Isabelle; Joly, Francisca
Summary: Introduction: Antioxidants essential trace elements (TEs), selenium (Se), zinc (Zn) and copper (Cu) are key dietary components and their supplementation in parenteral nutrition (PN) is recommended. However, the frequency of marginal deficiencies and related clinical outcomes remain poorly known in patients receiving long-term PN. Methods and objectives: We conducted a retrospective observational study whose aim was to determine in a cohort of patients ( n  = 73) with chronic intestinal failure (CIF) enrolled in a tertiary home PN center and receiving long-term PN with systematic multi-TE supplementation, the prevalence of low serum TEs levels. The goal was also to assess mid-term incidence of serious infection and its associated factors. Results: Among the 73 studied patients, 21.9%, 13.9% and 21.1% had low serum Se (<0.9 μmol/l), Cu (<12.7 μmol/l) and Zn (<12.5 μmol/l) levels, respectively. There was no difference between short bowel syndrome (SBS) and non-SBS patients. 30 patients had at least one of the three serum TEs levels under the cut-off values of deficiency. No specific disease and/or underlying intestinal anatomy were associated with low serum TEs concentration. Cumulative incidence rates of serious infection were 11.1% 95CI[5.7–21.0] and 19.5% 95CI[12.0–30.7] at 6 months and 1 year, respectively. Central venous catheter-related bloodstream infection was the most common infection. Low serum Se was independently associated with a higher risk to develop serious infection (HR 2.65 95CI[1.01–6.97]). Conclusion: Low serum TEs concentration is a frequent condition in patients with CIF even with systematic multi-TE supplementations. Se deficiency exposes to a greater risk of serious infection. This suggests that frequent TEs dosage in this population as well as individually tailored supplementation may be beneficial.